2013
DOI: 10.1557/jmr.2013.151
|View full text |Cite
|
Sign up to set email alerts
|

3D morphological evolution of porous titanium by x-ray micro- and nano-tomography

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…While the ISD obtained for ρ = 50% are symmetric with respect to κ 2 = −κ 1 line, it is no longer the case for lower volume fractions that contain less saddle-shape interfaces and more interfaces with κ 1 and κ 2 of the same sign (i.e., locally convex shape). This is also consistent with the results obtained in experiments [27,43] and in phase-field simulations for bulkdiffusion coarsening [30][31][32].…”
Section: B Morphological Evolutionsupporting
confidence: 92%
See 2 more Smart Citations
“…While the ISD obtained for ρ = 50% are symmetric with respect to κ 2 = −κ 1 line, it is no longer the case for lower volume fractions that contain less saddle-shape interfaces and more interfaces with κ 1 and κ 2 of the same sign (i.e., locally convex shape). This is also consistent with the results obtained in experiments [27,43] and in phase-field simulations for bulkdiffusion coarsening [30][31][32].…”
Section: B Morphological Evolutionsupporting
confidence: 92%
“…In addition, it was suggested that structures manufactured from dealloying can present significantly different topologies than the ones obtained from spinodal decomposition [53]. To account for these effects, a natural extension of this work will consist of taking more realistic initial microstructures, obtained either from numerical models [1,16,28] or from tomographic observations of dealloyed samples [26,27,43,51]. Another limitation of the present study is the weak surface energy anisotropy considered in Sec.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure continues to corrode and forms a bicontinuous 3D network of pores by 33 min [Fig. 3(c)], analogous to the dealloying process which forms nanoand meso-porous structures for functional applications (Erlebacher et al, 2001;Zhao et al, 2017Zhao et al, , 2019Chen-Wiegart et al, 2013). The corrosion process slows in 33-185 min [Figs.…”
Section: D Nano-tomography Under a Liquid Molten Salt Extreme Enviromentioning
confidence: 99%
“…21 For example, an Nb-Ni alloy was immersed in molten Mg where Ni atoms were dealloyed (i.e., dissolved in Mg), and removal of the Mg-Ni phase by immersing the composite in nitric acid leads to a porous Nb structure. 22 Porous Ti, 23 Fe, and Fe-Cr 24 have also been produced by a similar method.…”
Section: Introductionmentioning
confidence: 99%